Factors Influencing Investment Decision of Mutual Funds and the Role of Personality Traits in Their Perception among Retail Investors in Kerala - Abhijith; P. Balasubramanian (Communications of International Proceedings, 2020)
Behavioural Finance as a field has been making an effort to elucidate a litany of heuristics, prejudices, inefficiencies to make sense of price moments of financial instruments. This paper is an attempt to study the factors influencing investment decisions among retail investors in Kerala. Data was collected from respondents through questionnaire. Personality traits indirectly impacts how we use we existing set of information this study shed light on the impact of personality traits on investment decision.   It would help in better understanding even with near-universal access to information and necessary allied infrastructure the investment per capita remains low compared to the rest of India. It also attempts to observe the influence of extroversion and openness as personality traits on the perception of factors influencing investment decisions among investors. The significant factors that influence investment decisions are observed to make it easier for improving and getting more retail investors to invest in mutual funds.
Keywords: Mutual Funds; Kerala; Personality Traits; Investment Decision; Individual Investor